2013
DOI: 10.3126/jnps.v33i3.8385
|View full text |Cite
|
Sign up to set email alerts
|

Study of Renal Profile in Babies with Perinatal Asphyxia in a Tertiary Care Hospital: A Prospective Case Control Study

Abstract: Introduction: Perinatal asphyxia is one of the important causes of preventable cerebral injury occurring in the neonatal period. Kidney is one of the most commonly affected organs leading to renal functional abnormality and blood electrolyte imbalance. This was a prospective case control study done in the NICU and neonatal unit at a tertiary care hospital. The objective of this study were to detect renal functional abnormality and electrolyte imbalance (sodium and potassium) among babies with perinatal asphyxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…In this study, 36 (60%) of 60 asphyxiated babies were hyponatremic. In the current investigation, hyponatremia was the most common electrolyte anomaly, which was consistent with the findings of Roy et al 18 Hypernatremia is most common in extremely preterm infants due to high transepidermal water loss, which may be exacerbated by excessive sodium administration. The current investigation excluded extremely preterm newborns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, 36 (60%) of 60 asphyxiated babies were hyponatremic. In the current investigation, hyponatremia was the most common electrolyte anomaly, which was consistent with the findings of Roy et al 18 Hypernatremia is most common in extremely preterm infants due to high transepidermal water loss, which may be exacerbated by excessive sodium administration. The current investigation excluded extremely preterm newborns.…”
Section: Discussionsupporting
confidence: 92%
“…This pattern of hyperkalemia among moderate and severe case group members matched earlier research findings. 18,19 Only 1.6% of participants in the control group developed hyperkalemia, compared to 18.3% of people in the case group. Blood urea and serum creatinine were considerably higher among case study participants among the various serum electrolyte mean values.…”
Section: Discussionmentioning
confidence: 93%
“…Mean crea nine value was raised in the second day of life of studied neonates. According to the study done15 by Roy et al serum crea nine on day 1 was 1.14±0.57 and rd on 3 day of life 1.24±0.5 which is nearly similar to the present study. The mean serum crea nine value in the6…”
supporting
confidence: 92%
“…5 In a study by Roy et al the mean urine volume gradually decreased as HIE grading increased and it was statistically significant (p<0.05). 13 Also Rai et al in their study stated that mean urinary output in severely asphyxiated babies was significantly lower as compared to mildly and moderately asphyxiated babies (p<0.01). 18 Similar to the present study where mean urine output in HIE Grade I neonates was 1.5±0.38 ml/kg/ hour whereas in Grade II and Grade III mean urine output was 1.3±0.53 ml/kg/hour and 1.1±0.39 ml/kg/hour respectively.…”
Section: Discussionmentioning
confidence: 90%
“…11 Also in the study by Roy et al 31.25% cases had HIE Grade I, 40.62% had Grade II, and 28.12% patients had HIE Grade III. 13 Panthee et al observed 24.4%cases developed HIE Grade I, 23.17% developed HIE Grade II and the remaining 9.75% cases developed HIE Grade III. 14 In the present study, Grade I HIE was seen in 68.0% neonates, Grade II was seen in 22.70% and 9.30% cases had Grade III HIE.…”
Section: Discussionmentioning
confidence: 96%